The hollow of fear - Thomas, Sherry (Sherry M.) (Thomas, Sherry (Sherry M.). Lady Sherlock series., 2018)
"Charlotte Holmes, Lady Sherlock, returns in the Victorian-set mystery series from the USA Today bestselling author of A Conspiracy in Belgravia and A Study in Scarlet Women, an NPR Best Book of 2016. Under the cover of "Sherlock Holmes, consulting detective," Charlotte Holmes puts her extraordinary powers of deduction to good use. Aided by the capable Mrs. Watson, Charlotte draws those in need to her and makes it her business to know what other people don't. When the estranged wife of her dear friend Lord Ingram is discovered dead on his estate, all signs point to him as the murderer. With Scotland Yard closing in, Charlotte goes under disguise to find out the truth"--